2009
DOI: 10.1080/08037050903013899
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of diastolic dysfunction in elderly hypertensive patients using integrated Doppler echocardiography

Abstract: One third of elderly hypertensive patients with preserved systolic function had moderate-to-severe asymptomatic DD. More than half of the patients had EFP with normal mitral inflow pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…If BP can be decreased effectively, the left ventricle relaxing and filling can be improved by reducing the left atrial and end-diastolic pressure. 6 LCZ696 reduced the BP better than valsartan; however, regression results of the BP changes showed that the benefits for NT-proBNP and left atrial size reduction were independent of the lowered BP. 5…”
Section: Introductionmentioning
confidence: 84%
“…If BP can be decreased effectively, the left ventricle relaxing and filling can be improved by reducing the left atrial and end-diastolic pressure. 6 LCZ696 reduced the BP better than valsartan; however, regression results of the BP changes showed that the benefits for NT-proBNP and left atrial size reduction were independent of the lowered BP. 5…”
Section: Introductionmentioning
confidence: 84%
“…First degree (mild) diastolic dysfunction (DD) is defined as: E/A < 0.8, E/Ea < 8, DT > 200 msec and second degree (medium) DD as: 0.8 < E/A < 1.5, 8 < E/Ea < 13 and the DT is 160-200 msec. The criteria for third degree (severe) DD are: E/A > 2, E/Ea > 13, DT < 160 msec [67,68]. The diastolic dysfunction in cirrhosis is most pronounced in patients with ascites [28,53].…”
Section: Evaluation Of Diastolic Functionmentioning
confidence: 99%
“…Hypertension treatment is one of the most important factors in treatment of diastolic dysfunction [ 20 ]. Effective decrease of blood pressure reduces the left atrial and left end-diastole pressure, improves the LV relaxation and filling.…”
Section: Treatment Modalitiesmentioning
confidence: 99%
“…Phospodiesterase 5 inhibitors are considered to reduce LV and arterial stiffness, to improve the endothelial function and reduce the pulmonary vascular resistance /RELAX-study/ [ 10 , 26 ]. Alagebrium chloride is a new agent which, in experimental research in animals, was found to improve the ventricular and vascular compliance, to reduce the blood pressure and vascular stiffness [ 20 , 27 ].…”
Section: Treatment Modalitiesmentioning
confidence: 99%